KETAHANAN SOSIAL EKONOMI RUMAH TANGGA DALAM MENGHADAPI EKSPANSI PARIWISATA ANALISIS SOSIOLOGIS DI DESA TAMANSARI BANYUWANGI - Muhammad Iqbal (AT TAMKIN : Jurnal Pengembangan Masyarakat Islam dan Perubahan Sosial, 2026)
This study examines the socio-economic resilience of households in the face of tourism expansion in Tamansari Village, Banyuwangi, which is important considering the rapid development of the Ijen tourist area as a driver of rural socio-economic transformation. Tourism growth not only opens up economic opportunities, but also raises challenges in the form of social inequality and changes in societal values. Therefore, this study aims to analyze the conditions of household socio-economic resilience, identify the impact of tourism expansion, and examine the community's adaptation strategies in dealing with these changes. This study uses a qualitative approach with a descriptive method. Data was obtained through in-depth interviews, observations, and documentation of local communities, business actors, and village officials. Data analysis was carried out using the Miles and Huberman interactive model through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that tourism expansion has a positive impact in the form of increasing income and diversifying livelihoods, but also causing socioeconomic inequality. Household resilience is influenced by adaptability, social capital ownership, and access to economic resources. The adaptation strategies carried out include business diversification, the use of social networks, and household economic innovation. This research emphasizes the importance of inclusive and sustainable tourism development to strengthen the socio-economic resilience of rural communities.